2019
DOI: 10.1515/pteridines-2019-0013
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between serum homocysteine level and ulcerative colitis: A meta-analysis

Abstract: Background: The aim of the present meta-analysis was to investigate the correlation of serum homocysteine (Hcy) concentration and ulcerative colitis (UC) through pooling all the relevant publications. Methods The electronic databases of PubMed, EMBase, Web of Science, Google Scholar, CBM, and CNKI were systematic searched with the text words of homocysteine/Hcy, ulcerative colitis/UC, and inflammatory bowel disease. The correlation between serum Hcy and UC were demonstrated by stand mean difference (SMD) and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Several studies have reported significantly elevated levels of tissue and serum homocysteine in children and adults with UC[ 195 - 198 ]. A significant positive association between elevated homocysteine and UC was confirmed by two meta-analyses in 2011 and 2018[ 199 , 200 ]. Homocysteine inhibits GPx, the principal antioxidant enzyme system used by the cell to remove (neutralize) H 2 O 2 [ 201 , 202 ].…”
Section: Perfluorooctanoic Acidmentioning
confidence: 94%
“…Several studies have reported significantly elevated levels of tissue and serum homocysteine in children and adults with UC[ 195 - 198 ]. A significant positive association between elevated homocysteine and UC was confirmed by two meta-analyses in 2011 and 2018[ 199 , 200 ]. Homocysteine inhibits GPx, the principal antioxidant enzyme system used by the cell to remove (neutralize) H 2 O 2 [ 201 , 202 ].…”
Section: Perfluorooctanoic Acidmentioning
confidence: 94%
“…This allows increased ETC metabolism of reducing equivalents (NADH, FADH2) that generates additional H 2 O 2 . Finally, markedly elevated levels of tissue homocysteine have been reported in colonic mucosa of individuals with UC and a meta-analysis found that serum homocysteine levels were significantly higher in UC groups compared to healthy controls (P < 0.001) (Morgenstern et al 2003;Zhong et al 2019). Homocysteine is a potent oxidative stressor that increases H 2 O 2 in several ways.…”
Section: Ulcerative Colitismentioning
confidence: 99%